PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS UNTUK PENGELOLAAN PERKEBUNAN KELAPA SAWIT - Arif Imam Suroso; Kudang B. Seminar; Pramadia Satriawan (School of Business, Bogor Agricultural University (SB-IPB), 2004)
PT Astra Agro LestariTbk has a huge palm oil plantation that spread out in several locations inIndonesian's main island such Sumatra, Kalimantan, and Sulawesi. To manage theplantations, PT Astra Agro Lestari needs an information system, which isspatially referenced. The purpose of this study is to investigate and analyzethe operational plantation information according to user needs, and to developprototype of spatial information system. A modified method of Development LifeCycle (SDLC) and prototyping developed were used. The output of developedinformation system are some information products that consist of basicplantation, daily harvesting, fertlizing, plant disease, and plantationinfrastructure information such building, roads network, and bridges. The datawere collected from related divisions PT. Astra Agro Lestari and compiled intoboth spatial and attribute database. Spatial information system has an impactin the effeciency of processing time and cost increasing information quality,making problem solving easier.